Comparing the functional recognition of aesthetics, hydrology, and quality in urban stream restoration through the framework of environmental perception. (8th April 2019) - Hong, Chang‐Yu; Chang, Heejun; Chung, Eun‐Sung
Abstract: This study explores the application of a civic perception analysis in the context of stream restoration as a social‐ecological system (SES). Analysing such a SES is useful for understanding correlations between civic interests and environmental conditions in river restoration. An analytic hierarchy process (AHP) analysis was used to quantify the demand for restoration objectives. Additionally, an image‐based survey was used to precisely capture residents' perceptions of urban stream restoration by comparing aesthetic images, hydrologic functions, and environmental quality. Based on the AHP results, a hierarchical multiple regression was derived. A total of 181 participants responded to our survey, and the results were summarized by each subwatershed in the An'Yang watershed. The results demonstrated that the perceptions of residents who live in various environmental and regional conditions may manifoldly reflect their personal visual and aesthetic preferences by subwatershed. The upstream subwatershed values (SW1 = 7.86 and SW2 = 7.39) were higher than those in the downstream areas (SW5 = 5.28 and SW6 = 5.15). Consequently, this hierarchical multilevel model showed that individual environmental perception was highly associated with visual preference regarding stream restoration at the subwatershed level ( p  < 0.001). Urban environmental and spatial planners could use such information when restoring and designing waterfront spaces.